2023
DOI: 10.1111/nph.18813
|View full text |Cite
|
Sign up to set email alerts
|

Photographs as an essential biodiversity resource: drivers of gaps in the vascular plant photographic record

Abstract: The photographic record is increasingly becoming an important biodiversity resource for primary research and conservation monitoring. However, globally, there are important gaps in this record even in relatively well-researched floras.To quantify the gaps in the Australian native vascular plant photographic record, we systematically surveyed 33 sources of well-curated species photographs, assembling a list of species with accessible and verifiable photographs, as well as the species for which this search faile… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 47 publications
0
13
0
Order By: Relevance
“…Unlike structured surveys, where sampling time and intensity are often strictly controlled, community photograph data, and community science data more generally, are unstructured and prone to bias. This bias can manifest in multiple ways, such as most observations being made on weekends when users have more free time, more observations being made during warmer months, certain environments having more representation in data, and more records coming from developed areas where more people live, certain taxa being over- or under-represented, and observers not finding or reporting all species at a site (van Strien et al 2013b, Silvertown et al 2015, Troudet et al 2017, Callaghan et al 2021, Di Cecco et al 2021, Mesaglio and Callaghan 2021, Mesaglio et al 2023b). These biases are not likely to be an issue when using single or a few records for, for example, distribution.…”
Section: Resultsmentioning
confidence: 99%
“…Unlike structured surveys, where sampling time and intensity are often strictly controlled, community photograph data, and community science data more generally, are unstructured and prone to bias. This bias can manifest in multiple ways, such as most observations being made on weekends when users have more free time, more observations being made during warmer months, certain environments having more representation in data, and more records coming from developed areas where more people live, certain taxa being over- or under-represented, and observers not finding or reporting all species at a site (van Strien et al 2013b, Silvertown et al 2015, Troudet et al 2017, Callaghan et al 2021, Di Cecco et al 2021, Mesaglio and Callaghan 2021, Mesaglio et al 2023b). These biases are not likely to be an issue when using single or a few records for, for example, distribution.…”
Section: Resultsmentioning
confidence: 99%
“…Analyses have indicated that plants with different values for the traits in question (life history, growth form, and stem woodiness) exhibit different functional trade-offs (Šímová et al 2018;Vico et al 2016;Towers et al 2023). Similarly, plants with different values for these three categorical traits display different numeric trait-climate associations (Flores-Moreno et al 2019), require different conservation strategies (Mayfield, Ackerly, and Daily 2006), have different responses to key disturbances (Gallagher et al 2021;Clarke et al 2013), and even differ in the degree to which they have a public photographic record (Mesaglio et al 2023). Having complete tabular datasets for these traits across the Australian flora, therefore, has direct implications for the management and conservation of these species, in addition to facilitating more broad-scale biogeographic analyses.…”
Section: Discussionmentioning
confidence: 99%
“…Many additional studies will have chosen study taxa based on their scores for plant growth form, life history, and woodiness; this dataset represents a rapid way to scan a list of potential study taxa for appropriate study taxa. Within our research group, the plant growth form dataset has already been used twice (Towers et al 2023; Mesaglio et al 2023).…”
Section: Discussionmentioning
confidence: 99%
“…The plants were harvested on private land in Meridional Italy. Plant recognition application PlantNet was used for botanical identification [7]. The leaves were cleaned with distilled water and dried at 50 ± 1°C in a tray dryer (Melchioni Babele) for 6 h. The dried leaves were milled (Kenwood CH580), and sifted with a 500 µm sieve, obtaining plant powders.…”
Section: Preparation Of Vegetable Powders and Plant Extractsmentioning
confidence: 99%